REPRESENTASI BUDAYA LOKAL DALAM FILM DOKUMENTER: ADU KUDA, WARISAN ZAMAN KERAJAAN, EKSPEDISI PULAU MUNA - Wa Ode Nila Farlin (WELL-BEING: Journal of Social Welfare, 2023)
Documentary film are a medium for conveying information all at once and media for promoting local culture. This research aims to know how the representation of local cultural meanings in documentaries: Horse Fighting, Legacy of the Age of Empires, and Muna Island Expedition. This study uses qualitative research. The focus of this research is signs of film semiotics that display a culture that is packaged well and accepted by the audience. The research results show that the documentary film: Horse Fighting, Legacy of the Age of Empires, Muna Island Expedition has a broad meaning. This film lifts one of the cultures that are characteristic of the Muna people so that the wider community will get to know Muna culture, one of which is the tradition of horse fighting. This documentary film is a medium for conveying messages and disseminating information and as a promotional medium for local culture.